Potensi Daun Kelor (Moringa oleifera) Terhadap Kadar Kadmium Dan Kreatinin Dalam Darah Sebagai Indikator Kerusakan Fungsi Ginjal Pada Tikus Putih Yang Terpapar Asap Rokok - Christ Kartika Rahayuningsih; Riya Agustin; Tacik Idayanti (Universitas Muhammadiyah Surabaya, 2022)
High exposure of cigarettes in Indonesia causes various disturbances in the body's metabolism, especially in the kidney, which is due to the cadmium metal content. Cadmium induces oxidative stress by the formation of free radicals and decrease natural antioxidant activity in the kidney organs (nephrotoxic). One way to overcome nephrotoxic by decreasing blood creatinine, we can utilize Moringa oleifera (MO) which is known as a